The impact of geopolitical risk, economic policy uncertainty, and bitcoin on precious metals: Evidence from a dynamic simulated ARDL approach - Triki, Mohamed Bilel; Mohamed, Emad SuLiman Sharif; Ahmed, Sumaya Ibrahim; Jaghoubi, Salma (Edelweiss Applied Science and Technology, 2026)
This study examines the impact of macroeconomic uncertainty on the price movements of gold, silver, and Bitcoin to assess their effectiveness as safe-haven assets. Using daily data from 2010 to 2025, the research applies a dynamic simulated Autoregressive Distributed Lag (ARDL) approach. The methodology includes thorough stationarity testing and ARDL bounds testing to analyze long-term cointegration and short-term shocks. Results indicate that gold and Bitcoin have significant long-term cointegration with macroeconomic uncertainty. Gold reacts immediately and persistently to economic instability, while Bitcoin shows strong short-term responsiveness and sustained linkages. Conversely, silver shows no meaningful relationship with uncertainty, suggesting it is not a reliable hedge. The findings confirm that gold and Bitcoin are effective instruments during economic stress periods. The dynamic ARDL model captures these complex interactions, emphasizing that silver’s safe-haven properties are limited compared to gold and Bitcoin. Investors and policymakers should prioritize gold and Bitcoin for risk mitigation and portfolio diversification. These assets offer essential protection against macroeconomic instability, whereas silver should be approached cautiously in risk-averse strategies.